Oscillations of all solutions of iterative equations - Nowakowska, W.; Werbowski, J. (Нелінійні коливання, 2007)
Наведено достатнi умови коливання всiх розв’язкiв лiнiйних функцiональних iтерацiйних рiвнянь. The paper contains sufficient conditions for the oscillation of all solutions of linear functional iterative
equations.